A Posterior Rotational Flap Technique Using Distraction Osteogenesis for Unilateral Lambdoid Craniosynostosis. Issue 4 (June 2021) - Kamel, George N.; McKee, Ryan M.; Carbulido, Kristine; Modi, Rishi; Belza, Caitlyn; Ewing, Emily; Segal, Rachel M.; O'Connor, Alyson; Gholami, Parham; Ryan, Justin; Lance, Samuel H.; Gosman, Amanda A.
Abstract : Introduction: The craniofacial asymmetry seen in unilateral lambdoid craniosynostosis may not be effectively treated by posterior cranial vault remodeling, endoscopic suturectomy, and helmet therapy, or suturectomy and distraction osteogenesis alone due to limitations in soft-tissue envelope expansion and relapse of the deformity. The authors report a series of unilateral lambdoid craniosynostosis patients treated with a posterior rotational cranial-flap technique using internal distraction osteogenesis. Methods: Posterior cranial vault reconstruction combined with internal distraction was used, aided by preoperative virtual surgical planning. An in situ posterior rotational flap osteotomy was utilized to maximize dural preservation. Primary outcome measures included age-adjusted volume change and age-adjusted percent volume change per mm distraction. Distraction characteristics and perioperative characteristics were also assessed. Results: A total of 5 patients were identified. Mean predistraction intracranial volume was 1087.5 cc ( SD   =  202.3 cc) and mean postdistraction included intracranial volume was 1266.1cc ( SD   =  131.8cc). Mean age-adjusted percent included intracranial volume change was 14.1% ( SD   =  9.6%), and mean percent intracranial volume change per mm distraction was 0.43%/mm distraction ( SD   =  0.37%/mm distraction). One patient developed a distractor site infection postoperatively that was treated successfully with oral antibiotics. All patients had a Whitaker score of 1 at one year follow up. Conclusions: Posterior cranial vault remodeling using osteogenesis and a rotational cranial flap technique with dural preservation can be effectively used to maximize bone flap viability and limit postoperative relapse in patients with unilateral lambdoid craniosynostosis. Long term analysis as well as comparison to open techniques will need to be interrogated. Abstract : Supplemental Digital Content is available in the text